Nanostructured metal sulfides electrocatalyst for oxygen evolution reaction - Willson Nicholas (Nanyang Technological University, 2020)
The demand for energy so far has only been at an increasing rate, and this can be accounted for due to the rising population of the world. However, methods to meet the energy demand of the world has always deteriorated the environment. Such methods are not sustainable and other alternatives needs to be established to harness and store energy. One such way is to split water into hydrogen and oxygen. Hydrogen has really huge potential energy that one can utilize to harness energy. Combusting hydrogen to generate energy results in water byproduct, which is also environmentally friendly. However, one of the major drawbacks of obtaining hydrogen gas from water splitting is that the oxygen evolution reaction has high overpotential. This becomes a bottleneck to the overall efficiency of the reaction. To reduce the overpotential required, electrocatalyst is required. Various literatures have reported the use of IrO2 and RuO2 as the electrocatalysts for oxygen evolution reaction, however Ir and Ru are both rare earth metals and procuring them is costly. In this report, the author proposes nanostructured metal sulfides as the alternatives. The metal sulfides electrocatalysts will be synthesized in a laboratory and their performances will be evaluated using linear sweep voltammetry (LSV) and cyclic voltammetry (CV). Moreover, physico-chemical characterization of the electrocatalysts using x-ray diffraction (XRD) technique and scanning electron microscopy (SEM) will be done to observe their morphologies and analyze their elemental composition.